Protein-nucleic acid interactions and the expanding role of mass spectrometry. - Hanson, C; Robinson, C (2004)
Mass spectrometry methods are being developed that enable detection of protein interactions with nucleic acids. By mass measuring complexes a direct determination of the stoichiometry of protein-nucleic acid interactions is revealed. For more complex assemblies, using a different approach it is possible to gain information about subcomplexes and even the spatial arrangement of proteins in macromolecular machines. To illustrate these different approaches we review progress and problems encountered in evaluating complexes from bimolecular interactions through to macromolecular machines such as ribosomes.